Pemaknaan Pesan Dalam Komunikasi Digital : Studi Hermeneutik Pada Pengguna Media Sosial - Almadina Rakhmaniar (Lembaga Pengembangan Kinerja Dosen, 2023)
This research explores the meaning of messages in digital communication on social media through a hermeneutic approach. The findings show that message interpretation is strongly influenced by users' personal and social contexts, including cultural backgrounds, life experiences, and individual values. Algorithms that personalize content create 'filter bubbles' that narrow views and reinforce biases, while homogeneous online communities reinforce the meaning of certain messages in 'echo chambers'. Intercultural digital communication often suffers from misunderstandings due to differences in cultural norms and context, but users who frequently interact with other cultures show better adaptation. Emotion and empathy in digital communication often lack depth, with anonymity increasing negative behaviors such as cyberbullying. Social media enables the construction of digital identities and personal narratives that influence the meaning of messages. The implications of this research highlight the importance of digital literacy education, the development of fair algorithms, programs that support intercultural communication, and policies to address cyberbullying. This hermeneutic approach provides important insights for creating a more inclusive, empathetic and effective social media environment.